2007
DOI: 10.1080/00207450600936650
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aromatherapy Massage on Blood Pressure and Lipid Profile in Korean Climacteric Women

Abstract: This study investigated the effects of aromatherapy massage on the lipid profile and blood pressure in Korean climacteric women. A wait-listed control group, pretest-posttest design was used. The subjects comprised 58 climacteric women: 30 in the experimental group and 28 in the control group. Aromatherapy massage using lavender, rose geranium, rose, and jasmine was given to the experimental group only. Each massage session lasted 30 minutes, and was performed once weekly for two 8-week periods with self abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 9 publications
1
9
0
5
Order By: Relevance
“…Also, it has been found that lavender promotes the heart function and coronary blood flow (Bikmoradi et al, 2015). Several studies suggested that aromatherapy and massage had positive effects on physiologic parameter and the level of anxiety and depression (Chang, 2008;Edge, 2003;Hur et al, 2007). Moreover, the risk of hospitalization in the CCU among older patients is more than other groups of patients (Ancona et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been found that lavender promotes the heart function and coronary blood flow (Bikmoradi et al, 2015). Several studies suggested that aromatherapy and massage had positive effects on physiologic parameter and the level of anxiety and depression (Chang, 2008;Edge, 2003;Hur et al, 2007). Moreover, the risk of hospitalization in the CCU among older patients is more than other groups of patients (Ancona et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Women in middle age experience changes in the autonomic nervous system such as increases in adrenal cortex hormones and catecholamines, leading to increased BP and unsuccessful psychological management, which can have effects such as depression, anxiety, and insomnia [10, 11]. Recent research on the effects of aromatherapy on BP and sleep has targeted menopausal women [12], prehypertensive middle-aged women [13], and stage 1 hypertensive patients [14]. But there have been no studies using aroma massage and body cream as a method of aromatherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hur ve ark (2007), kadınlarda menopoz döneminde kan basıncını ve lipid profilini azaltmada aromaterapi masajının etkisini inceledikleri çalışmada, deney grubundaki kadınlara (n=30) 8 hafta boyunca haftada bir kez 30 dakika gül kokulu sardunya, lavanta, gül ve yasemin yağı kullanarak aromaterapi masajı yapılmış ve çalışma sonucunda aromaterapi masajının kan basıncını düşürdüğü ancak lipid mekanizmasını etkilemediği belirlenmiştir [36]. Diz OA'da ise lavanta yağı; ağrı kesici, rahatlatıcı ve sedatif olarak amigdala üzerine etki ederek bireylerdeki mevcut ağrıyı azalmaktadır [15,21].…”
Section: Lavanta Yağiunclassified